Selective Synthesis of Cyano-Functionalized 2-Aryl-4H-chromenes and 2-Amino-4H-chromene-3-carbonitriles by Catalyst-Tuned Reactions of 2-Hydroxychalcones with 2-Substituted Acetonitriles - Yin, Guodong; Shi, Houqiang; Xu, Liqianyun; Wei, Xianhong; Tao, Qing (Synthesis, 2013)
A selective synthesis of 4H-chromenes by the reactions of 2-hydroxychalcone derivatives with acetonitriles substituted with electron-withdrawing groups is described. Under catalyst-free conditions, the reactions give cyano-functionalized 2-aryl-4H-chromenes, whereas in the presence of sodium bicarbonate, 2-amino-4H-chromene-3-carbonitriles are obtained in excellent yields.
Keywords: heterocycles; nitriles; catalysis; chromenes